The Effect of Team Assisted Individualization Instructional Strategies to Enhance Problem Solving Ability, Learning Activity and Mathematics Learning Achievement - Qomariyah, Afifah Nur; Isnaini, Isnaini; Utami, Wikan Budi (FKIP Universitas Lampung, 2019)
The effect of team assisted individualization instructional strategies to enhance problem solving ability, learning activity, and mathematics learning achievement. Objectives: The purpose of this study is to determine the effectiveness of TAI learning medol on students’ ability to solve problems. Methods: The research method uses a quantitative approach with experimental research design. The research subjects involved 83 students of grade VIII at SMP Negeri 10 Tegal. Findings: The results of the proportion test on students using the TAI instructional strategies show that zcount > ztable (1.833 > 1.64), while the MANOVA test results show λcount < λtable (0.122 < 0.903), and the test results of τ2-Hotelling obtained Fcount > Ftable (8.63 > 2.76). Conclusions: The TAI instructional strategies is effective in improving problem solving skills, learning effectiveness, and mathematics learning achievement of students.Keywords: Team assisted individualization, problem solving ability, learning activity, mathematics learning achievement DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201904